Uji Korelasi Antara Debit Aliran Sungai dan Konsentrasi Sedimen Melayang pada Muara Sub DAS Padang di Kota Tebing Tinggi - Rian Asnul Maulana; Kemala Sari Lubis; Posma Marbun (Jurnal Agroekoteknologi, 2014)
Knowing about the problem of Watershed is very important to manage the river environment. Oneof the indicator to know the watershed problem is concentration of suspend load sediment.Thisresearch conduct to observe about relationship between stream flow debit and Suspend Load ofSediment which influenced hydrologic condition on Padang Hilir sub Watershed. This researchconduct to from May until October 2013 at Padang Hilir Sub Watershed, use a survey method withrandom sampling. Water sampling is taken out for three times in a week at after rain or no rain forsix months so that total water sample as much as 82 sample. The result show that concentration ofload sediment at no rain measure have highest value in October as big as 256,67 mg/L (worse)and the lowest in July as big as 43,3 mg/L (good),meanwhile at after rain and no rain measurehave highest value at August for 416,67 mg/L (very worse) and the lowest in July as big as 25mg/L (good). At no and after rain relationship betwen concentration of suspend load sediment andstream flow showed by equation : Y = 74,721 + 0,895x with signification value was 0,023 anddetermination value (r2) was 0,014 ( very weak). Meanwhile at not rain relationship betwenconcentration of suspend load sediment on stream flow regression showed by equation :Y = 28,741 +0,030x with stream flow signification value as big as 0,046 and determination value(r2) was 0,065 (weak).Key words : Padang Sub Watershed, stream flow, concentration of suspend load sedimen.